TABLE OF CONTENTS: VOLUME 14, NUMBER 8 (DECEMBER 2024) - Table of Contents, Volume 14 number 8, 2024 (African Journal of Social and Behavioural Sciences, 2024)
AFRICAN JOURNAL OF SOCIAL AND BEHAVIOURAL SCIENCES (AJSBS)